2014
DOI: 10.1080/00140139.2014.895054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of competing environmental variables and signage on route-choices in simulated everyday and emergency wayfinding situations

Abstract: This study examined the relative influence of environmental variables (corridor width and brightness) and signage (directional and exit signs), when presented in competition, on participants' route-choices in two situational variables (everyday vs. emergency), during indoor wayfinding in virtual environments. A virtual reality-based methodology was used. Thus, participants attempted to find a room (everyday situation) in a virtual hotel, followed by a fire-related emergency egress (emergency situation). Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 21 publications
1
55
0
Order By: Relevance
“…These distinctions are also reminiscent of the idea introduced by Carpman et al [13] that we have the environmental affordance (what the structure suggests can occur) and the manifest cues (e.g., signage) that are used to elucidate the floor plan configuration. Some research [29] has placed environmental affordances ( i.e. , corridor width, brightness) in direction competition with manifest cues ( i.e.…”
Section: Wayfindingmentioning
confidence: 99%
“…These distinctions are also reminiscent of the idea introduced by Carpman et al [13] that we have the environmental affordance (what the structure suggests can occur) and the manifest cues (e.g., signage) that are used to elucidate the floor plan configuration. Some research [29] has placed environmental affordances ( i.e. , corridor width, brightness) in direction competition with manifest cues ( i.e.…”
Section: Wayfindingmentioning
confidence: 99%
“…It is expected that this knowledge must be more fully discussed, before another similar tragedy happen 27 27 The last great fire tragedy in a nightclub with a lot of similarities to Boate Kiss happened in Romania, still not addressed. To illustrate, the following points can be raised: what would be the real contribution of the air conditioning system in the scattering of the smoke; environmental variables and others can significantly influence the route-choices [47][48][49], then what are the influence of each one the collective and environmental factors that caused people to move toward the bathroom instead of the exit; how realistic can one deal with accessibility and disability's issues for an evacuations in non-adaptive behaviour situation associated to a high population densities in a nightclub?…”
Section: Discussionmentioning
confidence: 99%
“…Without intervention from the environment, it has been suggested that travellers will turn to the right at a T-Junction, however it has been argued that driving habits may influence a traveller's decision to turn left or right at a T-Junction. 38,39 Other common natural paths include the path with the least angular deviation (i.e. keeping on a straight path), 2,30,37,40 or the path of least complexity (i.e.…”
Section: Tool Developmentmentioning
confidence: 99%
“…35,37,[41][42][43] Other natural path choices may include the widest option (i.e. following a wider corridor round rather than keeping to the straightest path), 38 or the most visibly accessible option. 5,7,44 Other metrics which are used to measure a spatial layout's ability to aid natural wayfinding and natural path-taking, include those measuring spatial connectivity and centrality, 40,42,[44][45][46] however, these measure the space or network graph as a whole.…”
Section: Tool Developmentmentioning
confidence: 99%